Measles Surveillance Attributes Assessment Based on Surveillance Officers’ Perception of Public Health Center in Surabaya - Bilqis Elfira Maharani; Arief Hargono (Jurnal Berkala Epidemiologi, 2014)
Measles is one of infectious diseases that potentially lead to death when complications occur. Surabaya is the area where the most measles cases occur in East Java. Surveillance as one of measles controlling efforts expected to provide qualified data and information as the basis for any decision making for a treatment or intervention. This study is a descriptive research aiming at evaluating the attributes of measles epidemiology surveillance system in Surabaya on 2012. The evaluation was done by assessing the attributes of surveillance then compared to technical guide for measles surveillance 2012, the decree of the health ministry of The Republic of Indonesia at 2003 about conducting surveillance system of health epidemiology guideline, and guidelines for evaluating surveillance systems from center for disease control and prevention 2001. The data collection method employed interview and observation or study documentation. The respondents of this study were 39 surveillance officers at 39 Public health center (PHC) in Health Department Surabaya working area. The variables of this study were simplicity, flexibility, data quality, acceptability, sensitivity, predictive value positive, representativeness, timeliness, and stability. The results of this study showed that the simplicity is complicated. The flexibility from case based measles surveillance is not flexible whereas the flexibility from early warning alert and response system is flexible. The data quality, acceptability, sensitivity and representativeness are low. The predictive value positive has not been able to be scored. The stability is high and the timeliness is punctual.